Impact of different fertilizers on soil solution and tomato growth - Canales-Almendares, Jorge Enrique; Borrego-Escalante, Fernando; Narvaez-Ortíz, Willian Alfredo; González-Morales, Susana; Benavides-Mendoza, Adalberto (Revista Mexicana de Ciencias Agrícolas, 2021)
Soil solution is a complex and open system that has inputs and outputs of energy, this study was carried out to determine the impact of different types of fertilizers on the composition of the soil solution and the accumulation of biomass in tomato plants. Tomato plants cultivated in greenhouse in pots with calcareous soil and forest soil were used to apply three types of fertilizers: Steiner solution, solid fertilizers and vermicompost tea. Concentrations of NO3-, K+, Ca2+, Mg2+, Na+ and SO42- in the soil solution increased over time, registering higher ion concentration values in the solid fertilizer (625, 183, 374, 70, 49 and 161 mg L-1, respectively) and in the Steiner solution (500, 177, 363, 65, 69 and 235 mg L-1). The highest concentrations of ions in the soil solution coincided with the largest accumulation of biomass, 3 938 and 4 546 g plant1 in the solid fertilizer and the Steiner solution, respectively. In contrast, in the soil solution of the vermicompost tea, except for Na+, there were lower ion concentrations (94, 63, 118, 28, 75 and 98 mg L-1) and a lower accumulation of biomass, with an average of 1 355 g plant-1. The Steiner solution and solid fertilizers treatments had the highest average yield values, with 3 637 and 2 712 g plant-1, respectively. This result indicates that the form of application and source of the fertilizer influences the soil solution.